Pendampingan Penerapan Pembelajaran Kooperatif untuk Meningkatkan Kemampuan Mengajar Guru di MIS Hidayat Probolinggo - Saila, Nurul; Jannah, Faridatul; Sulianti, Ani; Qomariyah, Ryzca Siti; Inayati, Tatik (EDUPEDIA Publisher, 2022)
The learning model used by the teacher is one of the factors that influence student learning outcomes. If the teacher in learning only applies one learning model, students will get bored in participating in learning. Boredom of students will reduce their learning motivation and reduce their learning outcomes. The problem that arises at MTs Hidayah Probolinggo is the low student learning outcomes in Mathematics. This is indicated by the low percentage of students who achieve KKM scores, some students who do not pay attention to the teacher while teaching, namely chatting with friends, falling asleep, playing with their stationery, etc. The results of interviews with several students, obtained information that the teacher taught using the lecture method only, which made them feel bored. From the results of the interviews with the teacher, information was obtained that the teacher taught using the lecture, question and answer and assignment methods, and the teacher had never used the cooperative learning model. This is due to the teacher's lack of understanding of various kinds of learning models. The purpose of this activity is to add to the teacher's insight about learning models that are able to activate students in learning by providing assistance to teachers in implementing cooperative learning. The implementation of this activity includes two activities, namely the socialization of cooperative learning models, which is carried out in a classical manner, to broaden teachers' insights about cooperative learning models and assistance in preparing lesson plans using cooperative learning models and their application in classroom learning, which is carried out individually. The achievement of this activity was that 100% of Hidayat's MIS teachers attended and were active in socialization activities of cooperative learning models, 83.3% of teacher-made lesson plans with cooperative learning model syntax and 84.2% of implementing cooperative learning according to lesson plans. Keywords: teaching skills, mentoring, cooperative learning.